TCSC Based Compensation with Genetic Algorithm Applied to the Optimal Reactive Power Flow Problem - GOUVEA, MAURY; dos Anjos, Jhenifer (INFOCOMP Journal of Computer Science, 2024)
In recent years, economic and environmental issues have shown the need to enhance the performance of power systems in order to postpone expansion investments. These issues have motivated research studies and technology developments to control the power flow, which allows better use of the current structure. One of these technologies is the Thyristor Controlled Series Compensation (TCSC), which permits a smooth control of the power flow throughout the transmission lines. This paper aims to analyze the performance of a TCSC device in power systems on the voltage stability and reactive power loss points of view. The proposed method uses a genetic algorithm to enhance the performance of power systems by adjusting the voltage magnitude of the controlled buses and the TCSC device. The results showed that the proposed method enhanced the voltage stability and decreased the total reactive power loss of the two standard IEEE systems, in the base case and contingencies.